Measurement of differential top-quark pair production cross sections in $pp$ colisions at $\sqrt{s}=7$ TeV - CMS collaboration (2199 authors) (2013)
Normalised differential top-quark-pair production cross sections are measured in pp collisions at a centre-of-mass energy of 7 TeVat the LHC with the CMS detector using data recorded in 2011 corresponding to an integrated luminosity of 5.0 fb(−1). The measurements are performed in the lepton+jets decay channels (e+jets and μ+jets) and the dilepton decay channels ( , μ (+) μ (−), and μ (±)e(∓)). The differential cross section is measured as a function of kinematic properties of the final-state charged leptons and jets associated to b quarks, as well as those of the top quarks and the system. The data are compared with several predictions from perturbative QCD calculations up to approximate next-to-next-to-leading-order precision. No significant deviations from the standard model are observed.